2021
DOI: 10.3389/fimmu.2021.705308
|View full text |Cite
|
Sign up to set email alerts
|

RGC-32 Acts as a Hub to Regulate the Transcriptomic Changes Associated With Astrocyte Development and Reactive Astrocytosis

Abstract: Response Gene to Complement 32 (RGC-32) is an important mediator of the TGF-β signaling pathway, and an increasing amount of evidence implicates this protein in regulating astrocyte biology. We showed recently that spinal cord astrocytes in mice lacking RGC-32 display an immature phenotype reminiscent of progenitors and radial glia, with an overall elongated morphology, increased proliferative capacity, and increased expression of progenitor markers when compared to their wild-type (WT) counterparts that make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In vitro experiments have demonstrated that RGC-32 KO brain astrocytes stimulated with TGF-β produce lower levels of extracellular matrix (ECM) components such as pro-collagen I, IV, and V; fibronectin; fibrillin; and fibulin, as well as proteoglycan core proteins such as heparan sulfate proteoglycan 2 (HSPG2), versican (VCAN), and testican (SPOCK3) ( 17 , 19 ). Mechanistically, RGC-32 physically associates with the transcription factor SMAD3 and is translocated to the nucleus through a process that requires SMAD3 phosphorylation and RhoA-Rho kinase activation ( 17 ).…”
Section: Astrocyte Emerges As An Important Contributor To the Develop...mentioning
confidence: 99%
See 4 more Smart Citations
“…In vitro experiments have demonstrated that RGC-32 KO brain astrocytes stimulated with TGF-β produce lower levels of extracellular matrix (ECM) components such as pro-collagen I, IV, and V; fibronectin; fibrillin; and fibulin, as well as proteoglycan core proteins such as heparan sulfate proteoglycan 2 (HSPG2), versican (VCAN), and testican (SPOCK3) ( 17 , 19 ). Mechanistically, RGC-32 physically associates with the transcription factor SMAD3 and is translocated to the nucleus through a process that requires SMAD3 phosphorylation and RhoA-Rho kinase activation ( 17 ).…”
Section: Astrocyte Emerges As An Important Contributor To the Develop...mentioning
confidence: 99%
“…In a quest to decipher the molecular networks underlying RGC-32’s ability to regulate astrocytic maturation and reactivity, we have performed next-generation RNA sequencing on brain astrocytes purified from WT and RGC-32 KO mice, under basal conditions and after TGF-β stimulation. We found that a lack of RGC-32 has a significant impact on the transcriptomic programs normally associated with brain development, neurogenesis, cell motility, and cell projection ( 19 ). Of special note is the fact that the differential regulation of pathways ontologically related to cell motility suggests that RGC-32 may be involved in astrocyte migration, as we have already described for other cell types such as endothelial cells and vascular smooth muscle cells ( 49 , 50 ).…”
Section: Astrocyte Emerges As An Important Contributor To the Develop...mentioning
confidence: 99%
See 3 more Smart Citations